When and Why Do Landlords Retain Property Investments? - Wood, G.; Ong, Rachel (Sage Publications Ltd., 2013)
This paper examines factors influencing Australian landlords’ decisions to retain their rental investments. A variety of statistical techniques are applied to uncover the factors precipitating the exit of landlords from rental housing markets. It is found that middle-aged investors are more attached to rental investments than younger investors. However, once retired, there is a sharp increase in the likelihood of exit from rental investments. The estimates also confirm the importance of financial variables. Leveraged loss-making investors with higher gross rental yields are more inclined to terminate leases. It is concluded that fiscal and monetary policy settings play an important role in shaping rental housing investment decisions, since interest rate and tax parameters are important in determining investors’ negative gearing status. These will in turn drive changes in housing supply and affordability in rental markets.